2009
DOI: 10.1080/13803390802317567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phonological and semantic cuing on encoding and retrieval processes in adolescent psychosis

Abstract: The aim of this study was to investigate the effects of cuing on encoding and retrieval processes in adolescent psychosis. Patients and controls were instructed to learn word lists under three conditions: no cue, phonological cue, and semantic cue. Memory performance was measured with free and cued recalls. In free recall, both groups showed higher performance with semantic than with phonological encoding cues, but patients had no advantage from semantic cuing relative to no cue, contrary to controls. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
2
5
0
Order By: Relevance
“…Words from the rhyme relationship displayed the worst memory performance. This is consistent with the results of the study by Doré et al (2009), which found that healthy controls remembered more words that were encoded in a semantic context than those that were encoded in a phonological context using both free and cued recall. Additionally, Kircher et al (2011) found that subjects were more successful in generating words in the same category of a target word than words that rhymed with a target word.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Words from the rhyme relationship displayed the worst memory performance. This is consistent with the results of the study by Doré et al (2009), which found that healthy controls remembered more words that were encoded in a semantic context than those that were encoded in a phonological context using both free and cued recall. Additionally, Kircher et al (2011) found that subjects were more successful in generating words in the same category of a target word than words that rhymed with a target word.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Martin et al (1999) provided evidence for this concept after observing that an anomic encephalitis patient's short-term memory was characterized by an ability to normally recall digits and nonwords (i.e., phonological information) but impairment in recalling words (i.e., semantic information). Furthermore, Doré et al (2009) demonstrated that healthy controls remembered more words that were learned in a semantic context (e.g., remembered “blueberry” when designated as a “fruit”) than those that were learned in a phonological context (e.g., remembered “bicycle” when designated as beginning with “bi”) using both free and cued recall. Additionally, Kircher et al (2011) found that individuals were able to generate more words that fit the category of a target word than words that rhymed with a target word in a set of verbal fluency tasks; the fMRI data collected in this study showed partially overlapping, but distinctive brain networks involved in this cognitive process including left inferior frontal gyrus, middle and superior temporal gyri, and the contralateral right cerebellum in generating rhyming and categorically related words, while rhyming showed additional activation in the left inferior parietal region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such disruption are the extra-list intrusions in free recall, which reflect misattribution of intemally produced words to the experimental Ust. Intrusions have been associated with hallucinations in adolescents with psychosis (Doré et al 2009) and with proneness to hallucinations in a non-cUnical sample (Brébion et al 2010fl). Moritz et al (2001) reported an association between intrusions and positive symptoms in a schizophrenia sample.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of a psychosis during this period is thought to affect differentially cognitive and clinical functioning in adolescent patients. Actually, some authors suggest that childhood or adolescent onset of psychosis would be associated with a lower cognitive performance when compared to adult‐onset (Basso, Nasrallah, Olson, & Bornstein, 1997; Doré, Caza, Gingras, Maziade, & Rouleau, 2008; Doré, Gingras, Caza, & Rouleau, 2007).…”
mentioning
confidence: 99%